Universal approaches to the treatment of acute respiratory viral infection and influenza - A. V. Mordyk; N. V. Bagisheva; T. S. Guseva; G. S. Bragina; M. V. Moiseeva (Лечащий Врач)
Background. In Russia, the number of people suffering from acute respiratory viral infection and influenza annually reaches more than 30 million people, and the annual total economic damage from acute respiratory viral infection is estimated at 40 billion rubles, accounting for about 80% of the damage from all infectious diseases and reaching up to 90% and more in the structure of infectious diseases. On average, an adult suffers from 2 to 4 colds during the year, a child gets sick from 6 to 9 times. A patient with acute respiratory viral infection and influenza needs effective outpatient treatment, since acute respiratory viral disease and influenza are accompanied by disability and are associated with a high probability of developing complications, including life-threatening ones. Of scientific and practical interest is the development of approaches to the treatment and prevention of acute respiratory viral infections in adults, which can be widely used on an outpatient basis. Objective. The purpose of the study was to evaluate the efficacy and safety of the use of interferon alpha-2b (rectal suppositories) for the treatment of acute respiratory viral infections and influenza in patients who sought medical help at the primary care stage.Materials and methods. A comparative, prospective, open study was conducted involving 60 patients with acute respiratory viral disease. Group 1 (n = 30) received interferon alpha-2b (rectal suppositories) 3 000 000 IU twice a day the treatment of the disease. In group 2 (n = 30) therapy was carried out in accordance with the recommendations for acute respiratory viral disease in adults of the Ministry of Health of the Russian Federation in 2022. Results. In group 1, there was a reduction in the period of fever (1.5 days shorter, relief of all symptoms was observed in an average of 7 days (in the comparison group for 9.5 days), the duration of days of disability was also 3 days less than in comparison group.Conclusion. the use of interferon alpha-2b (rectal suppositories) as part of the complex therapy of acute respiratory viral infections and influenza can reduce the treatment time, both in terms of accelerating the regression of symptoms and reducing the period of disability, which will improve the quality of life, reduce the likelihood of complications, reduce economic losses of the patient and society